Feeding infants below 29 weeks' gestation with abnormal antenatal Doppler: analysis from a randomised trial. Issue 1 (23rd August 2013) - Kempley, Stephen; Gupta, Neelam; Linsell, Louise; Dorling, Jon; McCormick, Kenny; Mannix, Paul; Juszczak, Edmund; Brocklehurst, Peter; Leaf, Alison; ,
Abstract : Objective: To describe feeding and gastrointestinal outcomes in growth-restricted infants <29 weeks' gestation and to determine the rate of feed advancement which they tolerate. Design: Analysis of prospectively collected data from a randomised feeding trial, the Abnormal Doppler Enteral Prescription Trial (ADEPT). Setting: 54 neonatal units in the UK and Ireland. Participants: 404 preterm, growth-restricted infants with abnormal antenatal Doppler studies from ADEPT. 83 infants <29 weeks and 312 infants ≥29 weeks' gestation were included in this analysis. Interventions: In ADEPT, infants were randomised to start milk 'early' on day 2 after birth, or 'late' on day 6. Subsequent feed advancement followed a regimen, which should have achieved full feeds by day 16 in the early and day 20 in the late group. Main outcome measures: Full feeds were achieved later in infants <29 weeks; median age 28 days IQR 22–40 compared with 19 days IQR 17–23 in infants ≥29 weeks (HR 0.35, 95% CI 0.3 to 0.5). The incidence of necrotising enterocolitis was also higher in this group; 32/83 (39%) compared to 32/312 (10%) in those ≥29 weeks (RR 3.7, 95% CI 2.4 to 5.7). Infants <29 weeks tolerated very little milk for the first 10 days of life and reached full feeds 9 days later than predicted from the trial regimen. Conclusions: Growth-restricted infants born <29 weeks' gestation with abnormal antenatal Doppler failed to tolerate even the careful feeding regimen of ADEPT. A slower advancement of feeds may be required for these infants. Trial registration number: ISRCTN87351483.